Monoamine transporters: insights from molecular dynamics simulations - Grouleff, Julie; Ladefoged, Lucy Kate; Koldsø, Heidi; Schiøtt, Birgit (Frontiers in Pharmacology, 2015)
The human monoamine transporters facilitate the reuptake of the neurotransmitters serotonin, dopamine, and norepinephrine from the synaptic cleft. Imbalance in monoaminergic neurotransmission is linked to various diseases including major depression, attention deficit hyperactivity disorder, schizophrenia and Parkinson’s disease. Inhibition of the monoamine transporters is thus an important strategy for treatment of such diseases. The monoamine transporters are sodium-coupled transport proteins belonging to the neurotransmitter/Na+ symporter (NSS) family, and the publication of the first high-resolution structure of a NSS family member, the bacterial leucine transporter LeuT, in 2005, proved to be a major stepping stone for understanding this family of transporters. Structural data allows for the use of computational methods to study the monoamine transporters, which in turn has led to a number of important discoveries. The process of substrate translocation across the membrane is an intrinsically dynamic process. Molecular dynamics simulations, which can provide atomistic details of molecular motion on ns to ms timescales, are therefore well-suited for studying transport processes. In this review, we outline how molecular dynamics simulations have provided insight into the large scale motions associated with transport of the neurotransmitters, as well as the presence of external and internal gates, the coupling between ion and substrate transport, and differences in the conformational changes induced by substrates and inhibitors.